Kinetika perubahan kualitas bawang merah (Allium cepa L.) varietas tajuk dibawah pengaruh edible coating dan suhu ruang penyimpanan - Randi Anggit Wibisono; Nursigit Bintoro (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Shallots (Allium cepa L.) is one of the important commodities to be developed because it has become a community need that is used as a spice in cooking and medicine. Post-harvest shallots require special treatment, because shallots are easily damaged and difficult to maintain in fresh form. In postharvest handling of fresh produce, coating on the fruit surface and storage room temperature is a good method for longer shelf life. This study aims to build a mathematical model on the storage of shallots by using a coating method made from carrageenan (seaweed) with variations in storage room temperature. Carrageenan concentrations used were 0 % (without treatment), 0.25 %, 0.5 %, and 0.75 %. While the storage temperature used is 5 oC, 15 oC, and 28 oC (room temperature). Mathematical models are used to predict the rate of change (k) in product quality and predict the value of physical quality parameters. Coated shallots and low-temperature storage showed better results on the rate of quality change in shallots which included (firmness, weight loss, total soluble solids, and degree of acidity). The validation test used included the value of the correlation coefficient (R2), P-value on X2 Chi-Square which indicates that the developed mathematical model can be used properly to predict the value of physical quality parameters in shallots